Beam delivery and final focus systems for multi-TeV advanced linear colliders. (1st May 2022) - White, G.; Gessner, S.; Adli, E.; Cao, G.J.; Sjobak, K.; Barber, S.; Schroeder, C.; Terzani, D.; van Tilborg, J.; Esarey, E.; Doss, C.; Litos, M.; et al.
Abstract: The Beam Delivery System (BDS) is a critical component of a high-energy linear collider. It transports the beam from the accelerator and brings it to a focus at the Interaction Point. The BDS system includes diagnostic sections for measuring the beam energy, emittance, and polarization, as well as collimators for machine protection. The length of the BDS increases with collision energy. Higher collision energies also require higher luminosities, and this is a significant constraint on the design for energy-frontier machines. Here, we review BDS designs based on traditional quadrupole magnets and examine the challenges involved in extending these to the Multi-TeV regime consistent with requirements for advanced accelerator concepts.